2012
DOI: 10.2151/sola.2012-020
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Strong Wind and Land Cover in Dust Source Regions on the Asian Dust Event over Japan from 2000 to 2011

Abstract: The relationship between the strong wind and land cover in dust source regions and the Asian dust event over Japan (ADE) was analyzed using the weather reports and coverage of the Normalized Differential Vegetation Index (NDVI) derived from the MODIS-Terra reflectance products during the spring (March to May) of 2000 to 2011. The target area for the dust source area in northeast Asia was defined as 35°N to 45°N and 100°E to 115°E as with Kimura (2012)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 21 publications
(36 reference statements)
0
10
0
Order By: Relevance
“…Previous observational and modeling studies have shown that variations in winds, temperature, soil moisture, and precipitation can influence dust emissions, transport, and deposition, as well as dust concentrations in East Asia [ Xuan and Sokolik , ; Wang et al , ; Gong et al , ; Hara et al , ; Kimura , ; Tan et al , ; Abulaiti et al , ] and in other parts of the world [e.g., Doherty et al , ; DeFlorio et al , ]. The interannual variation of winds is known to be the most important factor that influences dust concentrations over China.…”
Section: Introductionmentioning
confidence: 99%
“…Previous observational and modeling studies have shown that variations in winds, temperature, soil moisture, and precipitation can influence dust emissions, transport, and deposition, as well as dust concentrations in East Asia [ Xuan and Sokolik , ; Wang et al , ; Gong et al , ; Hara et al , ; Kimura , ; Tan et al , ; Abulaiti et al , ] and in other parts of the world [e.g., Doherty et al , ; DeFlorio et al , ]. The interannual variation of winds is known to be the most important factor that influences dust concentrations over China.…”
Section: Introductionmentioning
confidence: 99%
“…The area around Urmia Lake that was considered for this study has been selected based on remotely sensed NDVI values smaller than 0.2, which represent bare soil (Kimura et al, 2009; Kimura, 2012). It can be safely assumed that vegetated areas (NDVI ≥ 0.2) do not significantly contribute to dust generation (Jugder et al, 2014; Fan et al, 2014; Kimura and Shinoda, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…Small positive values indicate bare ground with little or no green vegetation, while values approaching 1 are a sign of lush green vegetation. [8] indicated that 0.05 ≤ NDVI < 0.2 is bare land or bare land surface with less vegetation, based on the [9]. The NDVI can be estimated from the reflectances of bands 3 and 4 using the following formula:…”
Section: Site Description and Analysis Methodsmentioning
confidence: 99%